Effect of Oxytocin Massage on Uterine Involution in Postpartum Mothers at Rengasdengklok Health Center, Karawang Regency - Armiyanti; Nurjanah (HM Publisher, 2023)
Background. After giving birth, the uterus will normally experience involution, which is the process of shrinking and returning to its pre-pregnancy size and shape. The process of involution involves uterine contractions, decreased blood flow, and the expulsion of unnecessary tissue. However, in case of failed uterine involution, the uterus cannot return to its normal size and shape in a timely manner, and leads to bleeding. This study aimed to determine the effect of oxytocin massage on uterine involution of postpartum mothers at the Rengasdengklok Health Center, Karawang Regency, Indonesia. Methods. This study was an experimental study, where as many as 30 research subjects participated in this study. Data analysis was performed bivariate to assess the effect of oxytocin massage on uterine involution. Results. The results of the study showed that the control group had a slower process of uterine involution compared to the intervention group, p-value 0.003 (p<0.05). Conclusion. It can be concluded that there is an influence between oxytocin massage and the uterine involution process.